Прізвища Горохівщини, похідні від назв тварин - Лісова, Лариса Олександрівна; Lisova, Larysa O. (Донецький національний університет, 2010)
Стаття присвячена дослідженню прізвищ Горохівщини, похідних від назв тварин (птахів, комах, плазунів, риб). Проаналізовано основні семантичні групи прізвищ.

This article deals with proper names of Volin region originated from names of animals (birds, insects, reptiles, fish). Main semantic groups of surnames analysed in this research.
Surname on the territory of Horohivshchyny derivatives from the names of animals
Keywords: антропонім; anthroponym; апелятив; appelative; прізвище; surname; мотиви номінації; motives of nomination